2021
DOI: 10.3390/pharmaceutics13101555
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics Identification of Potential Targets for Alzheimer Disease and Antrocin as a Therapeutic Candidate

Abstract: Alzheimer’s disease (AD) is the most frequent cause of neurodegenerative dementia and affects nearly 50 million people worldwide. Early stage diagnosis of AD is challenging, and there is presently no effective treatment for AD. The specific genetic alterations and pathological mechanisms of the development and progression of dementia remain poorly understood. Therefore, identifying essential genes and molecular pathways that are associated with this disease’s pathogenesis will help uncover potential treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 76 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, several van der Waals forces were found around the ligand backbones with the respective amino acid residues of receptors binding pockets would create strong cohesive environments, that stabilizes the receptor–ligand complexes. 75–77 Compared to epicatechin and procyanidin B2, the standard drugs acarbose and nicotinic acid demonstrated lower binding affinities to their respective receptors ( Figures 6 and 7 ). Altogether, our molecular docking analysis revealed that both epicatechin and procyanidin B2 has molecular properties to interact efficiently with cholinesterase, α-amylase and α-glucosidase, suggesting that these compounds are the bioactive components that could be responsible for the biological activities of AESTL reported in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, several van der Waals forces were found around the ligand backbones with the respective amino acid residues of receptors binding pockets would create strong cohesive environments, that stabilizes the receptor–ligand complexes. 75–77 Compared to epicatechin and procyanidin B2, the standard drugs acarbose and nicotinic acid demonstrated lower binding affinities to their respective receptors ( Figures 6 and 7 ). Altogether, our molecular docking analysis revealed that both epicatechin and procyanidin B2 has molecular properties to interact efficiently with cholinesterase, α-amylase and α-glucosidase, suggesting that these compounds are the bioactive components that could be responsible for the biological activities of AESTL reported in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that the AMPA receptor (GRIA4) was significantly up-regulated in the hippocampus of patients with AD ( Jacob et al, 2007 ). MAP2K4 was exhibited brain-specific gene and to play essential roles in the regulation of cell proliferation in AD ( Wu et al, 2021 ), while MAP2K4 was related with the condition and prognosis of endometrial carcinoma ( Zhang et al, 2022 ). ITPR1 ( Seo et al, 2020 ) and GABBR2 ( Yin et al, 2021 ) may be associated with AD, and prostate cancer ( Choi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 3D structures of sitagliptin (CID: 4369359), PNU-74654 (CID:9836739), and crizotinib (CID:116250) were retrieved from the pubchem database ( accessed on 22 October 2021), in the spatial data file (SDF) format, and consequently converted to PDB file format using the PyMOL visualization tool [ 61 ] ( accessed on 22 October 2021), while the crystal structures of DPP4 (PDB:2ONC), CTNNB1 (PDB:1JDH), and MET (PDB:3DKF) were downloaded from the protein database (PDB), ( accessed on 22 October 2021), in PDF file format. File preparation for molecular docking was as described in previous studies [ 62 , 63 , 64 ]. Using autodock software, an in silico molecular docking tool [ 65 ], all PDB files were converted to PDBQT file formats, and docking was accordingly performed using autodock, as described previously [ 66 , 67 ].…”
Section: Methodsmentioning
confidence: 99%